2020
DOI: 10.1017/dmp.2020.333
|View full text |Cite
|
Sign up to set email alerts
|

Association of Public Interest in Preventive Measures and Increased COVID-19 Cases After the Expiration of Stay-at-Home Orders: A Cross-Sectional Study

Abstract: Introduction: Following Stay-at-Home (SAH) orders issued for COVID-19, state-level economic concerns increased and many let these orders expire. As a method to measure public preparedness, we sought to explore the association between public interest in preventive measures and easing of SAH orders—specifically the increases in COVID-19 cases and fatalities after their expiration. Methods: Search volume collected from Google Trends for “hand sanitizer,” “social distancing,” “COVID testing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 12 publications
(14 reference statements)
1
16
0
Order By: Relevance
“…We observed similar results in the second PLifeCOVID-19 Study, in which higher percentage of respondents declared the introduction of supplementation with immune-related nutrients and compounds during the first wave of the pandemic (and lockdown), when COVID-19 cases and deaths in Poland were incomparably lower than in the second wave during autumn. Previous GT analysis and population-based studies revealed that the interests [ 48 , 49 , 50 ] and practices [ 51 ] of protective behaviors, such as hand washing or use of hand sanitizers increased after the COVID-19 outbreak. Moreover, undertaken of those health-protective behaviors was related to a variety of factors, including sociodemographic [ 51 , 52 , 53 ], psychological characteristic (e.g., emotion regulation [ 54 ]), perception of being at risk to get COVID-19 [ 54 ], media or social-media exposure and trust in information from media and other people (friends and bloggers) [ 53 , 55 , 56 ], and knowledge or beliefs about COVID-19 [ 53 ], however there is a limited number of studies comparing both waves of the pandemic [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed similar results in the second PLifeCOVID-19 Study, in which higher percentage of respondents declared the introduction of supplementation with immune-related nutrients and compounds during the first wave of the pandemic (and lockdown), when COVID-19 cases and deaths in Poland were incomparably lower than in the second wave during autumn. Previous GT analysis and population-based studies revealed that the interests [ 48 , 49 , 50 ] and practices [ 51 ] of protective behaviors, such as hand washing or use of hand sanitizers increased after the COVID-19 outbreak. Moreover, undertaken of those health-protective behaviors was related to a variety of factors, including sociodemographic [ 51 , 52 , 53 ], psychological characteristic (e.g., emotion regulation [ 54 ]), perception of being at risk to get COVID-19 [ 54 ], media or social-media exposure and trust in information from media and other people (friends and bloggers) [ 53 , 55 , 56 ], and knowledge or beliefs about COVID-19 [ 53 ], however there is a limited number of studies comparing both waves of the pandemic [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third, the country of study and the references. Category Proxy data type Country and reference Adoption of NPI Mobile phones and/or vehicles through location intelligence and measurement platforms USA [367] , [368] , [369] , [370] , [371] , [372] Twitter Twitter population [373] , [374] Wikipedia and Reddit Canada, Italy, USA, UK [375] Google USA [376] ; 130 countries [377] TV USA [378] Mobility changes Mobile phones and/or vehicles through location intelligence and measurement platforms USA [37] , [38] , [379] , [380] Facebook Italy [39] Citymapper app 22 countries [381] …”
Section: Measuring Npis Via Proxy Datamentioning
confidence: 99%
“…Here, we find articles aimed at quantifying the adoption of NPIs via proxy data such as mobile phones collected by location intelligence companies [367] , [368] , [369] , [370] , [371] , [372] , Twitter [373] , [374] , COVID-19 ad-hoc apps [196] , Wikipedia and Reddit [375] , Google [376] , [377] , and TV viewings [378] .…”
Section: Measuring Npis Via Proxy Datamentioning
confidence: 99%
See 1 more Smart Citation
“…More recently and more specifically related to the COVID-19 vaccines, rumors that COVID-19 vaccines cause infertility in women have circulated on social media [56]. Lastly, the politicization and polarization of news coverage surrounding the COVID-19 pandemic heavily influenced the public's attitude to COVID-19 response policies [55,[57][58][59][60]. Taken together, trouble with media outlets as trustworthy sources further supports the use of unbiased answer sources such as government agencies.…”
Section: Transparency and Quality Of The Answer Sourcementioning
confidence: 99%